Exploring Failure Orientation : Its Mediating Role in Multidisciplinary Teams of the Petroleum Industry - Mukherjee, Debasish; Arora, Nitin; Nath, Subash Chandra (Prabandhan: Indian Journal of Management, 2022)
Several factors that affect team effectiveness are listed in the literature on teams. This paper identified a new construct, “failure orientation,” which measured the collective capacity of a team to cope, learn, and develop from team failures. Qualitative research identified some interesting features of the “failure orientation” concept and its mediating role in teams’ input-mediator-output-input (I-M-O-I) model. The context was set in the Indian upstream petroleum industry, where failures are quite normal in oil-field operations. Learnings from such failures helped teams move forward to success in finding and producing crude oil and natural gas. The research methodology of conducting in-depth interviews of senior team leads and team members in two Indian public sector petroleum exploration companies was 80% of the industry activity. The findings enabled the development of a conceptual framework of failure orientation, which is a vital determinant of team effectiveness. The paper identified three categories (factors) of failure orientation for operationalizing this new construct: failure orientation in such multidisciplinary teams, that is, escapism, blame game, and collective analysis. The paper also positioned these as mediators in the I-M-O-I model of teams. Operationalization of the new construct would help practicing managers deal with teams encountering failures, which are frequent in this economically-vital petroleum industry. Further research with factor analysis could enrich the team literature significantly.